The smoke-free home study: study protocol for a cluster randomized controlled trial of a smoke-free home intervention in permanent supportive housing - Rachel Odes; Jessica Alway; Margot Kushel; Wendy Max; Maya Vijayaraghavan (BMC, 2022)
Abstract Background Formerly chronically homeless adults who live in permanent supportive housing (PSH) have high prevalence of smoking. It is uncommon to find smoke-free policies in PSH because of the concern that such policies contradict PSH's harm reduction framework and could increase homelessness should residents lose their housing because of the policy. However, in the absence of such policies, non-smoking PSH residents face the harmful effects of secondhand smoke exposure while residents who smoke see increased risks from high rates of smoking throughout their residence. Our pilot work highlighted the feasibility and acceptability of an intervention designed to promote voluntary adoption of a smoke-free home. Here we report a protocol for a cluster randomized controlled trial of the smoke-free home intervention for formerly chronically homeless residents in PSH. Methods The smoke-free home intervention provides face-to-face counseling and instruction to PSH residents on how to adopt a smoke-free home and offers training for PSH staff on how to refer residents to tobacco cessation services. We will randomize 20 PSH sites in the San Francisco Bay Area to either the intervention or wait-list control arms. We will enroll 400 PSH residents who smoke cigarettes in their housing unit and 120 PSH staff who work at the sites. At baseline, three- and six-months follow-up, we will ask residents to report their tobacco use and cessation behaviors and adoption of smoke-free homes. We will ask staff to answer questions on their knowledge, attitudes, practices, and barriers related to supporting residents' smoking cessation. The primary outcome for PSH residents is adoption of smoke-free homes for 90 days or more at six-months follow-up, and the secondary outcome is point prevalence tobacco abstinence. The primary outcome for PSH staff is change in Smoking Knowledge Attitudes Practices survey score. Discussion Voluntary adoption of smoke-free homes is a promising approach for reducing exposure to secondhand smoke and reducing tobacco use among a population facing high rates of tobacco-related disease, and is aligned with PSH's harm reduction framework. Findings from this study have the potential to inform adoption of tobacco control policies among vulnerable populations most at risk for smoking-related harms. Trial registration This study was registered with the U.S. National Institute of Health Clinical Trials register on April 22, 2021: NCT04855357.